Implementation of Waste Sorting Habits in the Buntet Islamic Boarding School Area - Ivan Chofyan; Agustina, Ina Helena; Mukhsin, Dadan; Rosenda, Diden; Yanto, Muhtadin; Kartaatmaja, Muhammad Alvianto (UPT Publikasi Ilmiah UNISBA, 2025)
The Buntet Islamic Boarding School has been established since 1750. Currently, the Buntet Islamic Boarding School has expanded promptly in terms of both education and distribution of its location. This development has a multiplier effect on the expansion of other activities, namely the service and trade industry sectors. As a result, there has been a huge increase in waste production in the Islamic boarding school and adjacent areas. Many studies on waste management have been conducted, but trash disposal management is linked to community habits and culture, thus the purpose of this research is to describe the application of waste sorting behaviors in the Buntet Islamic Boarding School region. The approach method used is: by collecting data through surveys and field observations, then analyzing the estimated waste generation at the study location and then analyzing waste selection. The application of voting habits is an innovative finding to be incorporated into the educational curriculum of an Islamic boarding school, so that it can provide a waste solution.